MANAJEMEN RISIKO BENCANA GEOLOGI - Bambang Sucipto Sucipto; Yuyun Mulyati Mulyati (KarismaPro, 2020)
Geological disasters can occur all over the world, including in this beloved Indonesian earth. There are many potential geological disasters in Indonesia, including landslides, flash floods, earthquakes, tsunamis, and volcanic disasters. The occurrence of geological disasters that occur especially in Indonesia can cause significant losses (risks). Various types of victims can be identified from each disaster incident. The amount of damage caused as a result of geological disasters, namely the worst is the loss of human life, then loss of property, as well as damage to the earth and the environment. The earth and the environment should be a unit that provides mutual benefits and does not give or cause harm.There are several Geological disasters that were previously unpredictable and occurred suddenly, for example the tsunami disaster in Aceh that occurred in 2006, and landslides that occurred in several regions in Indonesia. However, there are some natural disasters that can be predicted from the start, for example, the possibility of flash floods in an area due to environmental damage due to land conversion. Minimizing the victims of geological disasters can be done through analysis through risk management. Analysis through methods, strategies and policies will provide benefits for the government, society and other parties with the aim of being able to anticipate the risk of geological disasters in order to reduce losses. Environmental damage due to geological disaster needs to be rearranged according to functions that are more beneficial to human welfare